2020
DOI: 10.11648/j.eeb.20200504.11
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Improved Oat Varieties/Accessions at East Guji Zone, Oromia, Ethiopia

Abstract: The study was conducted with the objectives to introduce adaptive, high grain and forage yielder of improved Oat accessions/varieties for mid land of Guji zone, Oromia, Ethiopia. The experiment was conducted in Randomized Complete Block Design (RCBD) with three replications under Bore Agricultural Research Center, Adola sub site for two consecutive (2013/14 to 2014/15) in the mean season. Data of 50% date flowering, date of mature, biomass yield, plant height and diseases incidence were collected. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…This suggests that PH is influenced by both genotype and environmental factors, mirroring the results of Chairi et al (2020) and Yang et al (2021). Our findings also support the results of Dinkale et al (2020) and Tulu et al (2020), which both reported dissimilar agronomic and nutritional values of the same oat varieties grown in different locations. These alterations could be attributed to the reactions of different genotypes to variability in soil fertility, rainfall, and other climate conditions (Tulu et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that PH is influenced by both genotype and environmental factors, mirroring the results of Chairi et al (2020) and Yang et al (2021). Our findings also support the results of Dinkale et al (2020) and Tulu et al (2020), which both reported dissimilar agronomic and nutritional values of the same oat varieties grown in different locations. These alterations could be attributed to the reactions of different genotypes to variability in soil fertility, rainfall, and other climate conditions (Tulu et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In Ethiopia, oat (Avena sativa L.) is an important fodder crop. Its high tolerance to challenging abiotic conditions makes oat a viable crop in areas that are deemed marginal land due to soil type, temperature, and drought [4,5]. Ethiopia annually produces ~99,000 t of oat forage (adopted from [1] using harvest index of 1.5 [6]).…”
Section: Introductionmentioning
confidence: 99%